PELAKSANAAN PERLINDUNGAN HAK CIPTA BIDANG KARYA SENI MUSIK (Studi Kasus: Hak Mengumumkan di Kota Semarang) - , NANIES NURAINI HERDIRINA, SH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Copyright as an exclusive right that have meaning solely intended for the holder so that no one else should take advantage of these rights without the permission of the copyright holder. Implementation of copyright protection, especially in the field of art music in Indonesia is not optimal. Although legal protection arrangements regarding Copyright in Indonesia has been regulated by Law No. 19 of 2002 on Copyright, the implementation of copyright protection field of art music encountered some obstacles. This study identifies issues concerning copyright infringement or abuse of particular field of art music in Indonesia. The case study research is the implementation of the performing rights which occurred in Semarang city. The method of this study used empirical jurisdiction approach, this study was trying to synchronize implemented laws and regulations as stipulated in the Law on Copyright (Undang-undang Hak Cipta) with the rules of the law against the provisions stipulated by Yayasan Karya Cipta Indonesia and the application of legal rules fact in Semarang city. This is a descriptive analytical study that describing the provisions of the laws and regulations to the conditions that occur in the location of commercial establishments in Semarang which implementing the performing right of music. Based on these results, the protection of copyright as stipulated in the Copyright Act not implemented well in Semarang. Copyright Foundation works as an institution that has the role and authority in implementing copyright protection of works of the arts announced music at commercial places still have problems. So, we need a persuasive approach of the government to disseminate information and discussion on the provisions stipulated in the legislation, such as Yayasan Karya Cipta Indonesia to the copyright holder (user) and the creator itself. Keywords: copyrights protection, performing right, field of art and music